Exploring the pandemic: COVID-19 lockdown response levels as predictor of working memory performance and associated emotional responses - Oyejide, Aderemi Oyewunmi (University of the Witwatersrand, Johannesburg, 2023)
The unprecedented outbreak of the COVID-19 pandemic has altered the course of many lives, resulting in multiple health and social challenges. Due to the speed with which this andemic spread, various public health ‘lockdown’ measures were introduced to mitigate its spread. The outcome of adherence to these measures has revealed the possible influence on ndividuals varying cognitive abilities. Therefore, this study aimed at exploring the predicting relationship between lockdown responses to COVID-19 restrictions and working memory performance and associated emotional responses, while looking at the socio-demographic influences of age, gender, and level of education. Participants were drawn from a secondary dataset of an international online survey study of 1634 individuals between 18 – 75 years across 49 countries. Participants’ demographic questionnaires, working memory measures (free memory recall and digit span forward tasks), and hospital anxiety and depression scale were employed to collect data for analysis. A 4-way MANOVA and hierarchical multiple regression were utilised to explore the mean differences and predicting relationships between the study variables respectively. Significant differences were found in general memory performance, anxiety and depression scores across lockdown groups, but with no significant difference in working memory. The regression analysis indicated socio-demographic variables as non-predictive markers between lockdown responses and memory performance, while age and gender were significant predictors between lockdown responses and anxiety. The current study provides valuable information for interventions that may improve peoples’ psychological appraisals in preparation for any new potential waves or future pandemics.
A Research Report Submitted in partial fulfilment of the requirements for the Degree of Master of Arts in Social and Psychological Research (PSYC7022) in the Department of Psychology, School of Human and Community Development, Faculty of Humanities, at the University of the Witwatersrand, Johannesburg, in 2023.
Keywords: COVID-19 lockdown; Working memory; Depression; Anxiety; Public health measures; UCTD; SDG-3: Good health and well-being